1995
DOI: 10.1111/j.1365-2265.1995.tb01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen formation from androstenedione in human bone

Abstract: Oestrogens formed in human bone may play a physiological role in steroid hormone action in this tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…This is in part explained by the direct effect of oestrogen on the cell fate of MSCs towards either osteoblasts or adipocytes [101,102]. Of note, regulation of aromatase activity may provide another level of regulation of bone mass by marrow adipocyets because aromatase is highly expressed in bone marrow stromal cells [103][104][105][106][107][108]. Hence, it is possible that locally produced androgens and oestrogens in marrow adipocytes can exert regulatory actions on bone marrow cells including osteogenic cells.…”
Section: Marrow Fat and Osteoporosismentioning
confidence: 99%
“…This is in part explained by the direct effect of oestrogen on the cell fate of MSCs towards either osteoblasts or adipocytes [101,102]. Of note, regulation of aromatase activity may provide another level of regulation of bone mass by marrow adipocyets because aromatase is highly expressed in bone marrow stromal cells [103][104][105][106][107][108]. Hence, it is possible that locally produced androgens and oestrogens in marrow adipocytes can exert regulatory actions on bone marrow cells including osteogenic cells.…”
Section: Marrow Fat and Osteoporosismentioning
confidence: 99%
“…Frisch et al reported the production of estrogens from androgens in fatty marrow extracts isolated from femoral heads and iliac crests obtained from female subjects undergoing orthopaedic surgery [ 35 ]. Schweikert and Romalo demonstrated aromatase enzymatic activity and estrogen production in extracts prepared from ground trabecular bone tissues isolated from specimens obtained following hip replacement surgeries in male and female patients, and reported that the addition of aromatase inhibitors to these extracts inhibited estrogen production [ 36 ]. Sasano et al evaluated aromatase immunoreactivity and RNA expression via in situ hybridization and RT-PCR in bone tissue specimens including ribs, vertebrae and femurs from a series of 28 male and female patients undergoing orthopaedic surgery [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…E2 increases through aromatization of T during T replacement . Aromatase has been demonstrated in the testes, brain , adipose tissue , muscle , hair , bone , and vascular tissue . Eighty percent of circulating E2 is derived from peripheral aromatization of testicular or adrenal androgens.…”
Section: Discussionmentioning
confidence: 99%